Pelatihan asertivitas untuk menolak ajakan merokok pada anak (Universitas Islam Indonesia, 2026)
Children’s smoking behavior is influenced by several factors, one of which is their inability to display assertive behavior when invited to smoke by their peers. This community service program was conducted with children living in Lingkungan IV, Glugur Darat, Medan, Sumatera Utara. The children participated in an assertiveness training program adapted from the Anti-Drug Self-Resilience Module – Assertive Behavior Aspect developed by the Directorate of Information and Education for Prevention, National Narcotics Agency of the Republic of Indonesia (2021). The program was held over three days, consisting of six sessions, using a one-group pretest–posttest design. Its effectiveness was evaluated by examining differences in the children’s scores using a behavioral observation checklist. The results demonstrated that the program was effective in improving the children’s ability to assertively refuse invitations to smoke. Based on the Wilcoxon Signed-Rank Test analysis, all participants showed an increase in scores, with a significance value of p = 0.003 (p < 0.05). Qualitatively, the children who participated in the training also showed improvements in their ability to express appreciation and criticism, as well as in conflict management skills. They became more capable of delivering refusals politely while using more confident gestures.